Dari Dualisme ke Monisme: Transformasi Konsep Mens Rea dalam Kodifikasi KUHP di Negara-Negara Poskolonial - Kadir, Zul Khaidir (Jurnal Litigasi Amsir, 2024)
Postcolonial countries, including Indonesia, inherited criminal law imported from colonial powers, which in many schemes reflects a dualistic view of crime. In the dualistic approach, mens rea is seen as a separate element and needs to be evaluated separately from actus reus. However, in many countries that experienced colonialism, there was a tendency to abandon the concepts of man in strict conditions and move to a more monistic approach. This study uses a normative research method with a comparative approach. The data collection method was collected using literature studies (library research), then analyzed using qualitative methods and presented descriptively. The results of the study indicate that countries that inherited colonial legal systems tend to face a dilemma between maintaining a more idealistic dualism or adopting a more practical monism in dealing with increasingly varied crimes. This flexible and adaptive approach allows the criminal law system to achieve a balance between substantive justice and legal certainty, while ensuring that individual rights are respected in the law enforcement process.